Epidemiological investigation of a tularaemia outbreak after a hare hunt in Bavaria, Germany, 2018. (15th November 2021) - Böhm, Stefanie; vom Berge, Katharina; Hierhammer, Daniela; Jacob, Daniela; Grunow, Roland; Riehm, Julia M.; Konrad, Regina; Dauer, Marc; Bouschery, Berit; Hossain, Hamid; Schichtl, Elisabeth; Böhmer, Merle M.
Summary: In November 2018, a tularaemia outbreak occurred in Bavaria, Germany, among participants of a hare hunt and butchery employees handling the hares. We conducted an epidemiological outbreak investigation, including a retrospective cohort study among hunting participants, to identify likely transmission routes and activities associated with infection. Twelve of 41 participants were antibody‐positive for Francisella (F.) tularensis (attack rate: 29%). Cases reported influenza‐like symptoms ( n = 11), lymphadenopathy ( n = 1) and conjunctivitis ( n = 1). Infection only occurred in those hunting participants present while hares were processed, while risk of infection was highest when directly involved (RR = 10.0; 95%CI: 2.6–392). F. tularensis was isolated from 1/4 hares. Only two individuals reported using some of the recommended personal protective equipment (PPE). Occurrence of mainly non‐specific symptoms, likely due to early treatment, was not indicative of a specific transmission route. Transmissions via direct (skin/mucosa) contact and by inhalation of contaminated aerosols seem plausible. Promoting and increasing appropriate use of PPE among people processing hares is crucial to prevent future outbreaks.